2015
DOI: 10.3892/mmr.2015.3767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary trans-9 octadecenoic acid, trans-11 vaccenic acid and cis-9, trans-11 conjugated linoleic acid in mice

Abstract: Abstract. The aim of the present study was to investigate the effects of dietary trans fatty acids in mice. Following the administration of a 0.5/100 g diet of trans-9 octadecenoic acid (EA), trans-11 vaccenic acid (TVA) or cis-9, trans-11 conjugated linoleic acid (CLA) for 4 weeks, the body weights and the weights of the liver, testis and mediastinal adipose tissue (MAT) of the animals gradually decreased (P<0.05). The EA group exhibited the lowest levels of magnesium and triglycerides (P<0.05). CLA increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Additionally, the animals fed with either TFA had higher levels of IL-6 and IL-10, suggesting that both natural and industrial TFAs can facilitate LPS-stimulated immune response in this animal model [115]. Another model in male mice fed for 4 weeks with diets containing 0.5% w/w of TVA, EA or CLA9,11 showed that all TFAs used induced a reduction in body weight and adipose tissue, TVA induced a reduction in LDL cholesterol and TNF-α levels, while CLA9,11 induced higher levels of TNF-α [116].…”
Section: Studies In Experimental Animals (Table 6)mentioning
confidence: 76%
“…Additionally, the animals fed with either TFA had higher levels of IL-6 and IL-10, suggesting that both natural and industrial TFAs can facilitate LPS-stimulated immune response in this animal model [115]. Another model in male mice fed for 4 weeks with diets containing 0.5% w/w of TVA, EA or CLA9,11 showed that all TFAs used induced a reduction in body weight and adipose tissue, TVA induced a reduction in LDL cholesterol and TNF-α levels, while CLA9,11 induced higher levels of TNF-α [116].…”
Section: Studies In Experimental Animals (Table 6)mentioning
confidence: 76%
“…These could be the presence of different fatty acids which might enhance lipid oxidation, lower down lipid synthesis, and inhibit lipogenesis (Gao et al, 2009;Li et al, 2008). The effects of fatty acids on obesity were reported by different researchers (Miller, Stanton, & Devery, 2001;Wang et al, 2015). On the contrary, the serum HDL concentration was vividly increased after Tapra fish oil treatment.…”
Section: Discussionmentioning
confidence: 97%
“…(Table 2). Most predominant fatty acids in the Tapra fish oil were Octadecenoic acid and its derivatives which are known to modulate obesity and inflammation (Wang et al., 2015). In spite of the different habitat of Tapra fish (mainly found in Bay of Bengal and Indian Ocean), the fatty acid profiles of Tapra fish were comparable to the other studied sea fishes (salmon, herring, mackerel, anchovies, and sardines) found in Atlantic and Pacific Ocean (Bandarra, Marçalo, Cordeiro, & Pousão‐Ferreira, 2018; Jensen, Jacobsen, & Nielsen, 2007; Łuczyńska, Paszczyk, & Łuczyński, 2014; Öksüz & Özyılmaz, 2010; Sonavane, Koli, Patange, Naik, & Mohite, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, not every country pays attention to this problem, and EA may be ingested by us unconsciously. Meanwhile, recent studies have found that EA consumption in the diet has a negative impact on the oral condition of mice, associated with periodontal bleeding ( 28 ). And for patients after periodontal treatment, banning EA-rich food intake can improve the periodontal prognosis ( 29 ).…”
Section: Introductionmentioning
confidence: 99%